2017
DOI: 10.1093/nar/gkx570
|View full text |Cite
|
Sign up to set email alerts
|

The important conformational plasticity of DsrA sRNA for adapting multiple target regulation

Abstract: In bacteria, small non-coding RNAs (sRNAs) could function in gene regulations under variable stress responses. DsrA is an ∼90-nucleotide Hfq-dependent sRNA found in Escherichia coli. It regulates the translation and degradation of multiple mRNAs, such as rpoS, hns, mreB and rbsD mRNAs. However, its functional structure and particularly how it regulates multiple mRNAs remain obscure. Using NMR, we investigated the solution structures of the full-length and isolated stem–loops of DsrA. We first solved the NMR st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 46 publications
(75 reference statements)
0
23
0
Order By: Relevance
“…SL3 is a Rho-independent transcription terminator, which consists of many G-C base-pairs followed by multiple uridine nucleotides. SL2 contains a dynamic conformational equilibrium, so it can participate in base-pairing with hns , mreB , or rbsD mRNAs with different conformational states [ 59 ]. The SL1 and Linker 1 promote efficient translation of rpoS mRNA, which encodes for the stress sigma factor σ S , by acting as an anti-antisense RNA [ 54 , 60 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SL3 is a Rho-independent transcription terminator, which consists of many G-C base-pairs followed by multiple uridine nucleotides. SL2 contains a dynamic conformational equilibrium, so it can participate in base-pairing with hns , mreB , or rbsD mRNAs with different conformational states [ 59 ]. The SL1 and Linker 1 promote efficient translation of rpoS mRNA, which encodes for the stress sigma factor σ S , by acting as an anti-antisense RNA [ 54 , 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…The preferential Hfq-binding site of DsrA is Linker 1, while SL1 is partially destabilized by Hfq [ 62 ]. Meanwhile, recent NMR studies showed that SL1 has a very stable stem-loop structure, and cannot be significantly unfolded to base pair with the rpoS mRNA without Hfq at room temperature [ 59 ]. These results indicate that Hfq may play an important role in the unfolding of DsrA SL1.…”
Section: Introductionmentioning
confidence: 99%
“…Using this automated procedure we have successfully built 50 different small-RNA structures and analyzed some of their basic properties calculated from their dynamics data. Comparison of our server derived model of DsrA and the NMR structure of the SL1 of the DsrA (pdb code: 5WQ1)46 shows high similarities (RMSD: 2.75Å) between the structures, indicating reliability of our 3D model (FigureS7in Supplementary Information File). However, the NMR structure covers only a short fraction of the DsrA sequence.PresRAT enables a user to search for probable target mRNAs of sRNA sequences from a given bacterial chromosome and further concentrate on identification of the probable sRNA-mRNA binding regions.…”
mentioning
confidence: 79%
“…As per the latest RCSB protein databank 45 statistics, there are 1528 experimentally solved 3D structures of RNA representing only ~0.01% of the whole deposited structures. So far there is only one experimentally solved 3D structures available for sRNA 46 (N-terminal SL1 part of DsrA from E.coli) other than few sRNA conjugated with chaperone proteins [47][48][49][50][51] . PresRAT uses RNA2D3D 42 program to generate an initial RNA model followed by extensive refinement of the structure using GROMACS v4.6.3 molecular dynamics simulation package 52 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on sRNAs that recognize multiple targets have shown that interactions occur in different regions of the sRNA and that structural flexibility of the sRNA is required for interactions with different targets [ 38 , 39 ]. To analyze multiple interactions, we built density maps of the interactions.…”
Section: Discussionmentioning
confidence: 99%